(untitled) (American Journal of Islam and Society, 2015)
Dar al-Islam is the realized vision of an American-born Muslim, an Americaneducated Saudi businessman, the award-winning architect Hassan Fathy (1900-89). The purpose-built educational center and mosque was built in the early 1980s, sits in New Mexico’s mesa landscape, and today functions as an educational retreat. During the late 1970s Abdullah Nurdin Durkee and his wife Nura envisioned the construction of an Islamic village in the United States. During a trip to Makkah they met Sahl Kabbani, a Saudi businessman educated in the United States who felt a connection and desired to contribute in some manner. Together they decided to create an Islamic village that would also function as an educational center and retreat. Later on Nura Durkee, while also praying in Makkah, met Mothie and Johara, daughters of the Saudi king at the time, both of whom offered a financial gift to start the project. The group searched for a suitable site and eventually settled on Abiquiu, NM, due to the abundance of available land for a relatively low cost, the remote location, and the landscape’s similar qualities with those in the Middle East. In Abiquiu, 3,450 hectares were purchased in the rugged backcountry, populated with flat-topped mesas and a verdant valley near the Chama river. Abdullah Naseef, then rector of the King Abdul Aziz University in Jeddah, ...